Measuring The Unseen: Digitalization of Physics Diagnostic Assessment Based on Rasch Model - Nurani, Nena Setia; Rokhman, Fathur; Sarwi, Sarwi (Journal of Educational Sciences, 2025)
This study aims to develop a digital diagnostic assessment on the topic of work and energy using Rasch Model analysis. The instrument is designed to identify students’ misconceptions and learning difficulties more accurately. The research applies the Research and Development (R&D) approach with a modified 3-D model, consisting of four main stages: define, design, develop, and implementation. The validity and reliability of the instrument were analyzed using the Rasch Model through Winstep software. The results show that the instrument has a high validity level (V-Aiken > 0.8) and a strong reliability index of 0.89. The analysis also identified five items categorized as high-level, two as medium-level, and three as low-level instruments. Furthermore, the practicality test indicates that the instrument is easy to use, engaging, and accessible through multiple digital devices. Overall, the developed digital assessment tool proves to be effective in supporting teachers to conduct more efficient evaluations, providing a clearer understanding of students’ conceptual grasp in physics. This tool not only enhances the accuracy of assessment but also contributes to improving students’ comprehension of the work and energy concepts through interactive and technology-based learning approaches.